INNOVATIVE METHODS IN ASSESSING THE QUALITY OF PRESCHOOL EDUCATION - Turdalieva Sevara Adakhamjanovna (Bright Mind Publishing, 2026)
Quality assessment frameworks increasingly emphasize the importance of cultural and contextual relevance. Internationally recognized instruments must be adapted to reflect the unique values, customs, and developmental expectations of local populations. This adaptation ensures that assessments accurately reflect the lived experiences of children and families, promoting equity and inclusion. Culturally informed assessment involves close collaboration with families and communities, ensuring that evaluation criteria are both meaningful and respectful.
Keywords: Preschool education quality, innovative assessment methods, early childhood development, formative assessment, learning environment, inclusive education, teacher professional development, family engagement, quality indicators, educational policy.